PENGARUH KOMPETENSI GURU DAN TINGKAT SOSIAL EKONOMI TERHADAP KINERJA GURU SD MUHAMMADYAH 2 PONTIANAK - Aryani, Octavia Shinta; Mashudi, Mashudi; Asriati, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This study aims to identify and describe the Effects of Teachers on Teacher Performance Competency, Level Socioeconomic influences on teacher performance and teacher competence together Influence and socioeconomic level on teacher performance. This study was conducted in SD Muhammadiyah Pontianak 2 2013/2014 school year. This study used a descriptive method with a quantitative approach. Data collection techniques used are direct observation techniques; Direct communication techniques; indirect communication techniques; documentary study technique. Tools used for data collection was interview guide; questionnaires; and documentation. The results of his research is that there is a positive and significant effect of teacher competence terhadp teacher performance with a correlation coefficient 0.845 means to have a high impact; there is a positive and significant effect of socioeconomic level on teacher performance with a correlation coefficient 0.744 means to have a considerable influence closely; and there is a positive and significant effect of teacher competence and socio-economic level of the teacher's performance with regression coefficient simultaneously with the F value 71.237> 3.33 means that the value of the regression coefficient test simultaneously have a very high influence. Keyword: Teacher Competency